Efficacy of Ovsynch and Select-Synch Protocols to Improve Fertility in Anestrus Sahiwal Cows During Summer Season - Angadi, Sneha; Awasthi, Manoj Kumar; Parveen, Kaiser (The Indian Journal of Animal Reproduction, 2024)
The present investigation was carried out to evaluate the efficacy of ovsynch and select-synch protocols for improvement  of fertility in postpartum Sahiwal cows during summer season. Experimental animals (n=18) were equally divided into  three groups; each group consisting of 6 animals. Animals of ovsynch group were treated with standard G-P-G protocol  beginning from day 70 postpartum and FTAI was performed 14-20 hrs after second GnRH treatment. Animals of  select-synch group were treated similar to ovsynch group without second GnRH injection and they were inseminated at  detected estrus following AM-PM rule. Animals of this group, which did not show estrus signs up to 72 hrs after PGF2α  treatment, were inseminated with concurrent second injection of GnRH. No treatment was given to the animals of  control group and reproductive organs of animals were examined per rectum on days 80-82 for secondary signs of estrus  and A.I. was carried out in suspected estrus animals. The cyclic status of animals was assessed based on presence of CL on  ovary either on day 60 or 70 postpartum. Three cyclic animals got conceived in ovsynch group; while two cyclic animals  with detected estrus were conceived in select-synch group. Two cyclic and two acyclic animals in select-synch group were  inseminated at pre-determined time with concurrent GnRH injection and only one cyclic animal got conceived giving  overall conception rate of 50% (3 out of 6). In control group, one out of 6 animals got conceived yielding 16.66 per cent  of conception rate during experimental period. It may be concluded that ovsynch and select-synch protocols are effective  in cyclic than in acyclic animals.
Keywords: Anestrus; Ovsynch; Postpartum; Sahiwal; Select-synch; Summer